Influence of the observation angle target on efficiency classification of radar objects - M. V. Svinarsky; S. N. Yarmolik; A. S. Khramenkov (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
An influence of the observation angle on quality of the decisions about class object in solving the problem for radar recognition is considered. The program «Back Skattering Simulation» helped to receive radar range profile and radar spectral profile. The conditional probabilities of decisions were used as quality indicators of radar recognition.